Antecedents and Consequences of Endorsing Prescriptive Views of Active Aging and Altruistic Disengagement - de Paula Couto, M. Clara; Fung, Helene H.; Graf, Sylvie; Hess, Thomas M.; Liou, Shyhnan; Nikitin, Jana; Rothermund, Klaus (Frontiers in Psychology, 2022)
In this study, we investigated endorsement of two types of prescriptive views of aging, namely activation (e.g., prescriptions for older adults to stay fit and healthy and to maintain an active and productive lifestyle) and disengagement (e.g., prescriptions for older adults to behave altruistically towards the younger generation by granting young people access to positions and resources). The study comprised a large international sample of middle-aged and older adults (N = 2,900), covering the age range from 40 to 90 years. Participants rated their personal endorsement of prescriptive views of activation and disengagement targeting older adults in general (i.e., “In my personal opinion, older adults should…”). Findings showed that endorsement was higher for prescriptions for active aging than for prescriptions for disengagement. Age groups in the sample differed regarding their endorsement of both prescriptive views of activation and disengagement with older adults showing higher endorsement than middle-aged adults did. Prescriptive views of activation and disengagement related positively to each other and to the superordinate social belief that older adults should not become a burden, which attests to their functional similarity. In contrast, prescriptive views of activation and disengagement predicted psychological functioning and adaptation in opposite ways, with endorsement of active aging (vs. disengagement) being related to better (vs. worse) adjustment outcomes such as life satisfaction and subjective health. Our findings highlight the internalization of prescriptive views of aging in older people and their implications for their development and well-being.